Faktor yang Mempengaruhi Psychological Well Being Pada Orang Tua yang Memiliki Anak dengan Thalasemia: A Scoping Review - Priadi, Bambang; Mardhiyah, Ai; Rakhmawati, Windy (Universitas Malahayati, 2025)
ABSTRACT Thalassemia is a chronic condition that burdens the entire family. Parents with children with thalassemia experience critical psychological impacts, which cause deep anxiety, isolation, and self-neglect. To identify the description of PWB of parents with thalassemia children and the factors that influence it. Scoping review with Arksey & O’Malley framework. A literature search was conducted using three primary databases: EbscoHost: Medline Ultimate, Pubmed, Scopus, and one search engine, Google Scholar. The keywords were “Psychological Well-being OR PWB AND Parent OR Parental OR Family AND Thalassemia”. A total of 9 articles were analyzed. Several studies reported that there are still quite a lot of parents with thalassemia children who tend to have low PWB. Factors influencing the level of PWB are social activities, education, knowledge, economic status, self-acceptance, gratitude, religious practices, and effective coping strategies. Many parents experience psychological problems due to their child's illness. Psychological support for them is critical as part of comprehensive medical care along with clinical management for parents with children with thalassemia. Keywords: Psychological well being, Thalasemia, Parents ABSTRAK Talasemia merupakan kondisi kronis yang membebani kehidupan seluruh keluarga. Orang tua dengan anak penderita talasemia mengalami dampak psikologis yang kritis, yang menyebabkan kecemasan mendalam, isolasi, dan pengabaian diri. Untuk mengidentifikasi gambaran PWB orang tua dengan anak thalassemia dan faktor yang memengaruhinya. Scoping review dengan framework Arksey & O’Malley. Pencarian literatur dari tiga database utama: EbscoHost: Medline Ultimate, Pubmed, Scopus, dan satu search engine yaitu Google Scholar. Kata kunci yang digunakan adalah “Psychological Well-being OR PWB AND Parent OR Parental OR Family AND Thalassemia”. Sebanyak 9 artikel yang dianalisis. Beberapa studi melaporkan masih cukup banyak orang tua dengan anak thalassemia memiliki PWB yang cenderung rendah. Faktor yang dinilai memengaruhi tingkat PWB adalah aktivitas sosial, Pendidikan, pengetahuan, status ekonomi, penerimaan diri, rasa syukur, praktik keagamaan, dan strategi koping efektif. Banyak orang tua yang mengalami masalah psikologis akibat penyakit yang diderita anaknya. Dukungan psikologis bagi mereka sangat penting sebagai bagian dari perawatan medis yang komprehensif beserta manajemen klinis bagi orang tua dengan anak penderita thalassemia. Kata Kunci: Orang tua, Psychological well Being, Talasemia.